IMPLEMENTASI PROGRAM MA'HAD AL-HIKMAH DALAM MENINGKATKAN NILAI KARAKTER MANDIRI PADA SANTRIWATI MAN SIDOARJO - Nur Aulia, Mitha; Harmanto (Universitas Negeri Surabaya (Unesa), 2026)
This research aims to describe the implementation of the Ma'had Al-Hikmah program in increasing the value of independent character in female students at MAN Sidoarjo as well as identifying supporting and inhibiting factors in its implementation. This research used a descriptive qualitative approach with the subjects being caregivers, daily administrators and female students selected through purposive sampling. Data collection techniques through observation, interviews and documentation. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation and drawing conclusions. The theory used is Albert Bandura's social learning theory, where learning is through observation, imitation, and habituation to positive behavior. Apart from that, the character values ​​instilled reflect Imam Al-Ghazali's concept of moral education which emphasizes character formation through practice and example. The research results show that the Ma'had Al-Hikmah program is implemented through activities such as tahfidz classes, qira'atul poles, tahajud prayers, congregational prayers, daily pickets, ro'an, and takror. This program plays an important role in cultivating independent character values ​​in female students. Based on indicators of independence according to Sumarmo, female students show improvements in academic aspects (learning initiative and self-evaluation), emotional (self-control and self-confidence), social (responsibility and cooperation), and practical/physical (time management and not depending on other people). Supporting factors for this activity include the enthusiasm of the female students, cooperation with the management, and support from Ma'had facilities. Meanwhile, the inhibiting factors are limited facilities, busy activities, and lack of discipline on the part of female students and female students' guardians. Keywords: Program Implementation, Independent Character, Female Students, Character Building